Development of Arabic Language Modules Based on Local Wisdom and Moderation (Arabic and English Education Journal, 2025)
This article critically reviews the literature on the development of Arabic language modules that integrate local wisdom and religious moderation within the context of Islamic education. The urgency arises from the need for teaching materials that are not merely linguistic but also socially and ideologically relevant amid cultural diversity and the threat of radicalism. The study explores existing studies on Arabic language module development that incorporate values of local wisdom and religious moderation, identifies prevailing approaches, and highlights theoretical and practical gaps. This study employs a narrative literature review design. A total of 30 scholarly articles published between 2015 and 2025 were selected using national databases such as SINTA and other online repositories. Thematic analysis was conducted to examine methodologies, approaches, and integration forms. Findings reveal that local wisdom-based approaches increase student engagement and contextual relevance. Religious moderation values are beginning to appear in thematic content, though pedagogical and evaluative elements remain underdeveloped. Technological innovations like e-modules and mobile learning are effective technically but lack cultural and ideological depth. An integrative approach to Arabic module development—involving linguistic, cultural, and ideological dimensions—is necessary. Future field research should test the longitudinal effectiveness of such modules across various levels of Islamic education.